Factors associated with the cardiac allograft vasculopathy after heart transplantation. (25th November 2020) - Szczurek, W; Gasior, M; Skrzypek, M; Romuk, E; Zembala, M; Szygula Jurkiewicz, B
Abstract: Introduction: Cardiac allograft vasculopathy (CAV) is a major threat to long-term survival after heart transplantation (HT). The frequency of CAV is estimated to be 8% at 1 year after HT, 30% at the 5-year follow-up, and as high as 50% within 10 years after the procedure. Therefore, it is necessary to select those factors that are closely associated with the presence of CAV and facilitate the proper, fast and minimally invasive diagnosis of this disease. Purpose: The aim of this study was determine risk factors associated with CAV detection in patients after HT. Material and methods: We analyzed 299 consecutive patients after HT who underwent routine visits in our institution between 2015 and 2017. During the visit, echocardiography, routine coronary angiography, laboratory tests and immunosuppressive drug serum concentrations were performed in all patients. In addition, 10 ml of peripheral blood was collected to determine human interleukin 33 (IL-33) and IL-1 Receptor Like 1 (IL1RL1). IL-33 and IL1RL1 concentrations were measured by sandwich enzyme-linked immunosorbent assay (ELISA) with the commercially available kit. The diagnosis of CAV was based on the results of coronary angiography and defined according to the current International Society for Heart and Lung Transplantation (ISHLT) criteria.The Medical University Local Institutional Review Board approved the study protocol, and all patients provided informed consent. Results: Patients' median age was 59.00 (45.00–66.00) years, and 74.2% were men. The median time from HT to study inclusion was 9.03 (6.02–13.01) years. The frequency of CAV according to the ISHLT criteria in the analysed population was 47.5%. At the time of enrolment all patients were receiving immunosuppressive therapy with calcineurin inhibitor and mycophenolate mofetil, and were free from acute rejection (diagnosed either by echocardiography or biopsy), clinical signs of infection or symptoms of acute heart failure. Multivariate analysis using logistic regression confirmed that IL-33 OR 0.958 (0.944–0.972), p<0.0001 as well as IL1RL1 OR 1.061 (1.040–1.083), p<0.0001) serum concentrations, donor age OR 1.046 (1.009–1.085) p=0.015, left ventricular diastolic dimension OR 1.081 (1.016–1.149) p=0.015, and time from HT to blood collection OR 1.256 (1.151–1.371), p<0.0001 were independent factors of CAV detection. Conclusions: Lower IL-33 and higher IL1RL1 serum concentrations, as well as donor age, left ventricular diastolic dimension and time from HT to blood collection are independently associated with CAV. This study provides non-invasive, low-cost, and simple indicators for CAV detection. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Medical University of Silesia, Katowice, Poland